Concept of Increase Enrolment: Its effect on teachers in Ghana - Akoto-Baako, Hansen; Heeralal, Prem Jotham; Kissi-Abrokwah, Bernard (Richtmann Publishing, 2021)
This study investigated the effects of increase in enrolment on teachers in second cycle institutions in Ghana. The effects of increase enrolment on teacher’s work load, classroom management, health, social life and classroom interaction. The study employed the pragmatic paradigm and mixed method approach. Concurrent triangulation comprising descriptive survey for the quantitative phase and a case study for the qualitative phase. Self-developed questionnaire and semi-structured interview schedule were used to collect data from respondents. A total of hundred and forty-seven (147) respondents were used for the study. It was made up of one hundred and forty (140) teachers used at the quantitative phase and seven (7) head teachers used in the qualitative phase. The study found out that increase enrolment increased the workload of teachers significantly, and exposed teachers to health challenges. The study also revealed that increase enrolment made it very difficult for teachers to manage their classrooms and interact with students during instructional periods. The study recommended that teaching assistants be assigned to all teachers, government should set up a special body which is made up of occupational counsellors, psychologists, physicians who will tasked to organize programs on monthly bases to educate teachers on how to manage work related stress they encounter. Finally, the government should build more schools and make it a priority to train more teachers. Received: 15 September 2021 / Accepted: 16 October 2021 / Published: 5 November 2021